Opinion article: Neurosurgical treatment for neuro-ophthalmologic conditions - Williams, Zoe R.; Lee, Andrew G.; Fraser, Clare L.; Falardeau, Julie; Subramanian, Prem S.; Chen, John J.; Al Othman, Bayan; Dinkin, Marc J.; Mollan, Susan P.; Al-Zubidi, Nagham; Vates, Edward (Frontiers in Ophthalmology, 2023)
A significant role of the neuro-ophthalmologist is to counsel patients on appropriate management and anticipated visual prognosis for conditions affecting the afferent and efferent visual systems, including those requiring neurosurgical treatment. However, the literature regarding anticipated neuro-ophthalmologic prognosis after neurosurgical intervention for cerebral aneurysms, sellar lesions, optic pathway tumors, and elevated intracranial pressure is limited with many key questions unanswered. In order to optimize an interdisciplinary team approach to patient care, further studies of visual outcomes for neuro-ophthalmologic conditions requiring neurosurgical intervention are needed. The Research Topic Series "Neurosurgical Treatment for Neuro-ophthalmologic Conditions" highlights current studies of visual outcomes in these conditions.